Comparison And Evaluation Of Drought Indices Using Analytical Hierarchy Process (Ahp) Over Raichur District, Karnataka (MAUSAM, 2023)
The Raichur district is considered as a drought prone area in Karnataka. The study was carried out to compare and evaluate the performance of six drought indices in the study area namely Standardized precipitation index (SPI), Standardized precipitation evapotranspiration index (SPEI), China Z index (CZI), Deciles, Percent Normal (PN) and Rainfall anamoly index (RAI). A time series of six drought indices were compared and evaluated using histogram and analytical hierarchy process (AHP). The histogram of six drought indices showed that PN, Deciles and RAI showed higher frequency of extreme drought events which is considered as misleading in analysis. During the evaluation of the indices no bias was done between the indices. SPI and CZI moved to the top rank mainly due to their robustness and sophistication in nature. Whereas, PN moved to the second position mainly because of its higher simplicity compared to other indices with a score of 18.49 (SPI), 18.10 (PN) and 17.99 (CZI). The SPEI was observed to score higher in robustness and sophistication, due to lack of tractability and transparency was observed to be lagged.  Furthermore indices like RAI and deciles were observed to score very good rank under transparency and tractability. PN was observed to least in robust, thought the PN has scored the 2nd position it is highly not recommended for adaptation for the studies due to its unreasonably capturing of extreme droughts.  Looking over all pros and cons of all indices SPI was evaluated as perfect index for the selected study area.